THE FIRST SUNDAY LAWS AND THEIR ESCHATOLOGICAL COUNTERPART - Chrissutianto, Donny (Klabat Theological Review, 2021)
Most Christians challenge the idea of Adventist’ view regarding the eschatological Sunday law. They think that this concept is absurd and has no historical connection. This article examines how the first Sunday laws in the fourth and fifth century were conducted. It also surveys Ellen White’s understanding on the eschatological Sunday law. This comparison study attempts to see whether Adventist’s understanding represented by Ellen White’s writings is supported by historical facts or only a theoretical delusion. Based on three indicators about what was the main factor, who was the main actor and the executor. This research finds there is a similarity between the first Sunday laws and its eschatological counterpart. It shows that Adventist’ idea on the last Sunday law has historical pattern in the church history and not merely an illusion theory. Keywords: Sunday Law, Ellen G. White, Adventist, eschatology, early church